Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.24136/oc.2018.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative advantages in Polish export to the European Union ? food products vs selected groups of non-food products

Abstract: Research background: Globalisation and economic integration are the reasons for which the competitiveness of economic entities is analysed more and more often in the context of their relations with the international market. One of the ways to assess the competitiveness of the Polish food sector is an analysis of comparative (relative) advantages in the export of this sector’s products. Purpose of the article: The objective of this paper is to assess comparative advantages in Polish export of food product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The impact of Brexit on the agricultural sector is conditioned by the degree of future trade competitiveness (i.e. relative tariffs) and trade openness between EU and Britain (Szczepaniak, 2018;Vitunskiene & Serva, 2015). It also depends on the status of the sub-sector concerned (agriculture, fishery, organic farming and etc.…”
Section: Theoretical Discussion On the Effect Of Brexit Onto Capmentioning
confidence: 99%
“…The impact of Brexit on the agricultural sector is conditioned by the degree of future trade competitiveness (i.e. relative tariffs) and trade openness between EU and Britain (Szczepaniak, 2018;Vitunskiene & Serva, 2015). It also depends on the status of the sub-sector concerned (agriculture, fishery, organic farming and etc.…”
Section: Theoretical Discussion On the Effect Of Brexit Onto Capmentioning
confidence: 99%
“…For example, the agribusiness sector is essential for exports in developing countries (Matkovski et al , 2021). Works like those by Szczepaniak (2018) in Poland or by Sachitra and Chong (2018) in Sri Lanka have testified to this importance. In particular, Brazil has progressed from being an importer to being the world's third-largest exporter of food, agricultural raw materials and other agro-industrial products (Rodrigues and Marta-Costa, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies conducted to date frequently used one of the indicators of revealed comparative advantages, i.e., the Balassa Revealed Comparative Advantage Index (RCA), which is a ratio of the share of export of the analyzed product in world/regional trade to the share of export of the entire sector in world/regional trade [57]. This measure in the analyses of international competitive position of the agri-food sector was applied by previous studies [58][59][60]. A drawback of the Balassa index is connected with the estimation of comparative advantages only based on the value of exports.…”
Section: International Competitiveness Of the Agri-food Sector In The...mentioning
confidence: 99%
“…A weakness of RCA is also connected with its non-symmetric distribution and a lack of a finite upper limit [60,69]. In order to eliminate this problem several modifications have been developed for the Balassa index formula, providing its symmetric distribution [70,71].…”
Section: International Competitiveness Of the Agri-food Sector In The...mentioning
confidence: 99%